2011
DOI: 10.1016/j.contraception.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of out-of-pocket expense on IUD utilization among women with private insurance

Abstract: Background The study was conducted to evaluate the impact of out-of-pocket expense on intrauterine device (IUD) utilization among women with private insurance. Study Design We reviewed the records of all women with private insurance who requested an IUD for contraception from an urban academic gynecology practice from May 2007 through April 2008. For each patient, we determined the out-of-pocket expense that would be incurred, and whether she ultimately had an IUD placed. The total charge for placement of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 10 publications
1
41
0
Order By: Relevance
“…In a recent review of barriers for adolescents interested in LARC, reported mean out-of-pocket expenses for those without insurance for a LARC device and insertion exceeded $1,000 (Eisenberg, McNicholas, & Peipert, 2013). Another analysis found that in patients with insurance coverage, the amount of copays can profoundly decrease rates of obtaining an IUD, because those with copays that exceeded $50 were 11 times less likely to obtain an IUD (Gariepy, Simon, Patel, Creinin, & Schwarz, 2011). The Contraceptive Choice Project, although not focused on a postpartum population, has achieved greater than 75% LARC usage rates by eliminating nearly every barrier mentioned by participants in this study (Secura, Allsworth, Madden, Mullersman, & Peipert, 2010) and other published reports from the Contraceptive Choice Project cohort has demonstrated LARC's cost effectiveness (Winner et.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent review of barriers for adolescents interested in LARC, reported mean out-of-pocket expenses for those without insurance for a LARC device and insertion exceeded $1,000 (Eisenberg, McNicholas, & Peipert, 2013). Another analysis found that in patients with insurance coverage, the amount of copays can profoundly decrease rates of obtaining an IUD, because those with copays that exceeded $50 were 11 times less likely to obtain an IUD (Gariepy, Simon, Patel, Creinin, & Schwarz, 2011). The Contraceptive Choice Project, although not focused on a postpartum population, has achieved greater than 75% LARC usage rates by eliminating nearly every barrier mentioned by participants in this study (Secura, Allsworth, Madden, Mullersman, & Peipert, 2010) and other published reports from the Contraceptive Choice Project cohort has demonstrated LARC's cost effectiveness (Winner et.…”
Section: Discussionmentioning
confidence: 93%
“…Though not measured directly in this study, cost and access may also contribute to differences in providers' and patients' contraceptive choices. LARC uptake has been shown to increase when cost barriers are removed or reduced [17,18]. This survey was conducted in 2013, shortly after a provision of the Affordable Care Act (ACA) granted privately insured women access to birth control with no out-of-pocket costs.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 LARC methods often entail high initial costs, including for privately insured women, 15 and some data suggest that higher costsharing is a deterrent to LARC use. 6,16,17 However, other major barriers to LARC use exist in the United States, including patient and provider knowledge and attitudes regarding contraception in general and IUDs in particular. 18 Existing data are insufficient to accurately predict the impact of out-ofpocket cost elimination on LARC use nationally.…”
mentioning
confidence: 98%